2019
DOI: 10.1186/s12879-019-4132-y
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of metagenomic next-generation sequencing for identifying Streptococcus pneumoniae in paediatric bacterial meningitis

Abstract: Background There is currently no research on the diagnostic value of metagenomic next-generation sequencing (mNGS) for a single pathogens in CSF. The aim of this study was to analyse the value of mNGS for identifying Streptococcus pneumoniae ( S. pneumoniae ) in paediatric bacterial meningitis. Methods Bacterial meningitis (BM) cases from October 23, 2014, to December 31, 2016, and December 1, 2017, to July 31, 2018 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 30 publications
(26 reference statements)
3
44
0
Order By: Relevance
“…A second important consideration is the patient's exposure to antimicrobials before the sample was obtained. Although pathogen specific PCR and mNGS can detect residual microbial nucleic acid even after antibiotics have decreased the yield of culture 14,43,44 , a negative mNGS result needs to be interpreted with caution in this context. Finally, if a patient's infection is compartmentalized (for example, brain abscess) or if the suspected pathogen is typically diagnosed by serology because of a low abundance or absence in the CSF (such as Borrelia burgdorferi (Lyme disease) or Treponema pallidum (syphilis)), a negative CSF mNGS result should be interpreted with caution 14 .…”
Section: Metagenomics For Neurological Infectionsmentioning
confidence: 99%
“…A second important consideration is the patient's exposure to antimicrobials before the sample was obtained. Although pathogen specific PCR and mNGS can detect residual microbial nucleic acid even after antibiotics have decreased the yield of culture 14,43,44 , a negative mNGS result needs to be interpreted with caution in this context. Finally, if a patient's infection is compartmentalized (for example, brain abscess) or if the suspected pathogen is typically diagnosed by serology because of a low abundance or absence in the CSF (such as Borrelia burgdorferi (Lyme disease) or Treponema pallidum (syphilis)), a negative CSF mNGS result should be interpreted with caution 14 .…”
Section: Metagenomics For Neurological Infectionsmentioning
confidence: 99%
“…Studies for sequencing-based diagnosis of meningitis are ongoing all over the world. [27][28][29] However, the sequencing methods and bioinformatics pipelines used for the diagnosis are different in different studies. This is because sequencing technology, as well as bioinformatics technology including genome databases, has progressed quickly, making it difficult to establish standards.…”
Section: Discussionmentioning
confidence: 99%
“…Studies for sequencing‐based diagnosis of meningitis are ongoing all over the world . However, the sequencing methods and bioinformatics pipelines used for the diagnosis are different in different studies.…”
Section: Discussionmentioning
confidence: 99%
“…mNGS consists of agnostic DNA, RNA, or total nucleic acid sequencing followed by bioinformatic classification of sequence reads against databases of known organisms. Applications of this approach have ranged from the detection of occult pathogens during fulminant infection ( 3 ), chronic disease monitoring in at-risk populations like Cystic Fibrosis patients ( 8 ) and diagnosis of infection following antibiotic exposure ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only a few clinical mNGS assays are currently available from commercial or academic providers ( 3 , 11 ), and their clinical utility remains uncertain ( 5 ). Recent studies examining the performance characteristics of mNGS for pathogen detection have estimated clinical sensitivity above 70% ( 1 , 10 ) and specificity approaching 99% ( 1 , 12 ). Nevertheless, other large, longitudinal studies of mNGS have demonstrated positivity rates at 32% ( 6 ), 49% ( 13 ), or 61% ( 4 ).…”
Section: Introductionmentioning
confidence: 99%